2021
DOI: 10.1088/1742-6596/2145/1/012062
|View full text |Cite
|
Sign up to set email alerts
|

Color measurement of yellow sapphire by UV-Vis reflectance spectroscopy

Abstract: Yellow sapphire is a gemstone variety of corundum (Al2O3). The yellow color is commonly caused by Fe3+ impurity substituting for Al3+ in the Al2O3 structure. The depth of yellow color is linked to Fe3+ concentration. The higher content of Fe3+ produces a deeper yellow color. However, there is low content of the impurity such as Be2+ in cooperating with the low content of Fe3+ to produce the yellow color in yellow sapphires. It is difficult to differentiate between the natural yellow sapphire caused by high Fe3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Since the color observation by the naked eyes with GIA gem set could not be properly acceptable. Because of no red color appearance, we found that there were weak fluorescence due to low Cr 3+ in the samples [24]. The CIELAB color indices of sapphire samples using colorimeter as shown in table 2 presented L * , a * and b * .…”
Section: Resultsmentioning
confidence: 89%
“…Since the color observation by the naked eyes with GIA gem set could not be properly acceptable. Because of no red color appearance, we found that there were weak fluorescence due to low Cr 3+ in the samples [24]. The CIELAB color indices of sapphire samples using colorimeter as shown in table 2 presented L * , a * and b * .…”
Section: Resultsmentioning
confidence: 89%